Anxiolytic, memory improvement, hepatoprotective, and antioxidant effects of Thymus vulgaris on alcohol withdrawal syndrome in mice - Nadège Emégam Kouémou; Franklin Mbeboh Savo; Simon Pale; Aimé Paul Noubissi; Sylviane Mireille Nguepi Dongmo; Germain Sotoing Taiwe; Elisabeth Ngo Bum (Shahrekord University of Medical Sciences, 2024)
Introduction: Thymus vulgaris is a plant used in Cameroon to alleviate and treat hangover symptoms. This study was conducted to assess the anxiolytic, memory-improving, hepatoprotective, and antioxidant effects of T. vulgaris on alcohol withdrawal syndrome. Methods: In this preclinical study 42 mice were grouped into seven equal sets of normal control, negative control, positive control (piracetam; 200 mg/kg), and test (T. vulgaris; 25, 50, 100, or 200 mg/kg) groups. All mice (except those of the normal control) were administered ethanol by gavage once daily for 28 days. After alcohol withdrawal, behavioral assessments (elevated plus maze, Y-maze, and open field) were performed from day 29 to day 31, one hour following appropriate treatments. Mice were euthanized on day 32 and the brains and the livers were used for histopathological assessment and oxidative stress parameters evaluation. Results: In the elevated plus maze test, T. vulgaris at 100 and 200 mg/kg significantly (P < 0.001) increased the number of entries and the time spent in the open arms. The plant extract (200 mg/kg) significantly (P < 0.001) increased the spontaneous alternation percentage in the Y maze. T. vulgaris administration decreased malondialdehyde (MDA) and nitric oxide (NO) in the brain and liver and increased glutathione (GSH) and catalase (CAT). The plant extract reduced the neuronal degeneration and hepatocyte damage induced by chronic alcohol administration. Conclusion: T. vulgaris had anxiolytic, memory-enhancing, and hepatoprotective properties against alcohol toxicity. These results may justify the use of thyme in traditional pharmacopeia in the management of alcohol use disorders (AUDs).